2016
DOI: 10.1002/bjs.10274
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility work to inform the design of a randomized clinical trial of wound dressings in elective and unplanned abdominal surgery

Abstract: BackgroundDesigning RCTs in surgery requires consideration of existing evidence, stakeholders' views and emerging interventions, to ensure that research questions are relevant to patients, surgeons and the health service. When there is uncertainty about RCT design, feasibility work is recommended. This study aimed to assess how feasibility work could inform the design of a future pilot study and RCT (Bluebelle, HTA ‐ 12/200/04).MethodsThis was a prospective survey of dressings used to cover abdominal wounds. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…23 Table 1 illustrates the characteristics of 13 document types, including 5351 articles (84% of the 6397 documents) with the number of authors per publication ( APP ) of 5.6. The largest number of authors in the article is “Feasibility work to inform the design of a randomized clinical trial of wound dressings in elective and unplanned abdominal surgery” 24 published by 92 authors. The document type of the book chapters had the highest CPP 2020 of 112, which can be attributed to three highly cited book chapters with a TC 2020 of 100 or more, 19 by Reneker et al, 25 Muzzarelli and Muzzarelli, 26 and Klemm et al 27 with a TC 2020 of 498, 405, and 332, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…23 Table 1 illustrates the characteristics of 13 document types, including 5351 articles (84% of the 6397 documents) with the number of authors per publication ( APP ) of 5.6. The largest number of authors in the article is “Feasibility work to inform the design of a randomized clinical trial of wound dressings in elective and unplanned abdominal surgery” 24 published by 92 authors. The document type of the book chapters had the highest CPP 2020 of 112, which can be attributed to three highly cited book chapters with a TC 2020 of 100 or more, 19 by Reneker et al, 25 Muzzarelli and Muzzarelli, 26 and Klemm et al 27 with a TC 2020 of 498, 405, and 332, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Participants are randomised to one of three standard dressing groups: simple dressing (the comparator, believed to represent usual care [ 17 ]), no dressing or glue-as-a-dressing.…”
Section: Methodsmentioning
confidence: 99%
“…below skin level). A recent survey found that glue-as-a-dressing is a dressing strategy that is often used by general surgeons [ 17 ] but it is considered here as one of the two interventions, compared with a simple dressing (the comparator). Table 2 shows examples of commonly available tissue adhesives that can be used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wound infection or surgical site infection (SSI) occurs in up to 40% of open abdominal operations [1]. It can increase the length of time a patient stays in hospital, increase patient dissatisfaction and litigation, and it may impair oncological outcomes.…”
Section: Introductionmentioning
confidence: 99%